Strategies of non-arabic students in learning Arabic through Wiki Programme (Arabic article). - Nurkhamimi Zainuddin; Muhammad Feham Muhammad Ghalib (Faculty of Education, UKM,Bangi, 2012)
This study employs an experimental and evaluation method in conducting its research procedures. The theoretical foundation of the study was profoundly based on the theory of social constructivism proposed by Vygotsky (1978). The researcher examined ways of learning Arabic writing skills using the Wiki service among the students, their learning strategies, and motivations. Twenty five second-level students from the Department of Laws, Center for Foundation Studies, International Islamic University Malaysia participated in the study which was carried out during the semester two of 2008/2009 academic year. The students are all Malays. The researcher also discussed in details the steps of operating the Wiki service, and tools for evaluating the success of the program. The researcher found that the Wiki helps in facilitating the acquisition of writing skills among the non-Arabic students particularly in assisting them developing their ideas during initial phase of acquiring the skills. The results also indicated that the Wiki service is a successful program in the processes of teaching and learning Arabic writing skills, since most of the students obtained good results in their Arabic writing tests conducted throughout the study. They also suggested that the students in this study employed cognitive strategies more in their process of acquiring the language. The outcome of the students’ motivations analysis proposed the use of Wiki as a tool for enhancing their writing skills as they are found to be highly motivated and engaged in the learning process which in turn contributes positively to their learning process.